"Defectus discretionis iudicii, incapacitas assumendi i gravis timor reverentialis" w świetle wyroku Roty Rzymskiej c. De Lanversin z 19 stycznia 1994 r. - Góralski, Wojciech (Ius Matrimoniale, 2013)
This decision refers to a marriage contracted between Bernard and Martyna on 11 October 1969 (in Paris), which lasted for about ten years and then, on 21 January 1983 the man applied to the tribunal in Paris for annulment of the marriage due to his defectus discretionis iudicii and wife’s incapacitas assumendi. On 15 January 1987 the tribunal issued the pro nullitate decision only for the latter reason. After the appeal of the defender of the matrimonial tie to the tribunal of the second instance (in Versailles), on 17 May 1989 a negative decision for the appealed reason (Martyna’s incapacitas assumendi) was issued. After that Bernard appealed to the Roman Rota and on 24 April 1991 c. Lanversin bench proceeded to trial for three reasons for annulment of the marriage: 1) the respondent’s incapacitas assumendi (examined in the third instance); 2) the petitioner’s defectus discretionis iudicii (examined in the second instance); 3) the petitioner’s gravis metus reverentialis (added reason and examined in the first instance). On 19 January 1994 the Negative ad omnia decision was issued.